Aliscans: Das altfranzösische Heldenepos nach der venezianischen Fassung M. - Knapp, Fritz Peter (De Gruyter, 2013)
For the first time, this volume presents a German translation of the Old French heroic epic Aliscans, which served as a template for Wolfram von Eschenbach's novel in verse, Willehalm, one of the most important works of the German Middle Ages and in world literature. The primary source for the text is the edition based on the Venetian manuscript M (Holtus 1985). This is the version that is closest to Wolfram's template. This aim is to allow students of German studies to directly compare the two works. Such a comparison reveals the strongly derivative content of Wolfram's novel, along with the
Description based upon print version of record
Keywords: Electronic books; Deutsch; Übersetzung; Aliscans